2011
DOI: 10.1177/0961203310389097
|View full text |Cite
|
Sign up to set email alerts
|

The development of a simple questionnaire to screen patients with SLE for the presence of neuropsychiatric symptoms in routine clinical practice

Abstract: Aim:The creation of a physician-administered questionnaire to screen patients with Systemic Lupus Erythematosus (SLE) for the presence of symptoms suggestive of neuropsychiatric involvement (NPSLE). Methods: The development of the questionnaire followed three phases. First, a list of manifestations was prepared based on the ACR case definitions for NPSLE. A first questionnaire was constructed including 119 items. To reduce their number, a Delphi analysis was carried out and a second questionnaire with 62 quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Thus, it would be preferable to utilize comprehensive screening tools for mood, cognitive function, headaches, and autonomic function using standard and validated rating scales, 3,9–12 but this may not be logistically possible for routine screening.…”
Section: Symptoms Of Npslementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it would be preferable to utilize comprehensive screening tools for mood, cognitive function, headaches, and autonomic function using standard and validated rating scales, 3,9–12 but this may not be logistically possible for routine screening.…”
Section: Symptoms Of Npslementioning
confidence: 99%
“…Several diagnostic instruments have been proposed that implement shortened versions of standard neurologic and psychiatric exams to indicate the presence of neuropsychiatric symptoms in SLE patients, 35,12 but many of the proposed diagnostic scales have yet to be validated, and some are more sensitive to dysfunction in specific behavioral domains (such as depression). 13 …”
Section: Symptoms Of Npslementioning
confidence: 99%
“…Mosca et al developed a simple self-assessment screening tool for NPSLE in routine clinical practice with 27 questions for the 19 ACR NPSLE syndromes that capture sub-clinical involvement. 46 A score above 17 was considered as suggestive of the presence of NPSLE with a sensitivity of 92.9% (95% CI 85.1%–97.3%) and specificity of 25.4% (95% CI 14.7%–39.00%). Efforts have been made to validate it in different countries.…”
Section: Npsle: Screening Diagnosis and Monitoringmentioning
confidence: 99%
“…In children, the one study that investigated a cognitive symptom questionnaire showed it was unable to detect disease [60]. In adults, symptom questionnaires have proven more useful as markers for NPSLE, with reported high sensitivity for the presence of disease, but only modest specificity [61]. For depression and anxiety, there are several validated and established screens that may be self administered and can be used in children or adolescents, including the Children’s Depression Inventory [62], the Patient Health Questionnaire-9 for depression [63], the Screen for Child Anxiety Related Disorders [64] and the Generalized Anxiety Disorder 7-item scale for anxiety [65].…”
Section: Experimental Biomarkersmentioning
confidence: 99%